1999
DOI: 10.1088/0953-4075/32/7/015
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of electron-impact excitation of H(1s) into the states using a two-dimensionalR-matrix propagator

Abstract: Electron-impact excitation of the ground state of hydrogen into the states is studied by propagating the R-matrix in the two radial dimensions. Integral cross sections and resonance parameters are presented for collision energies from 0.75 Ryd (the n = 2 threshold) up to 0.96 Ryd (the n = 5 threshold). Below the n = 3 threshold, there is very good agreement with results from other methods and with experimental data. Between the n = 3 and n = 4 thresholds, integral cross sections are in better agreement with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…Apart from Aggarwal et al (1991), these calculations have focused on transitions between the ground state and terms up to the n = 3 shell. An exception is Dunseath et al (1999) who have employed a novel two-dimensional R-matrix propagator technique to study resonance widths in a small energy band below 0.96 Ryd. However, in general, excitation data involving the n = 3, 4, 5 and 6 shells are sparse in energy or incomplete in transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from Aggarwal et al (1991), these calculations have focused on transitions between the ground state and terms up to the n = 3 shell. An exception is Dunseath et al (1999) who have employed a novel two-dimensional R-matrix propagator technique to study resonance widths in a small energy band below 0.96 Ryd. However, in general, excitation data involving the n = 3, 4, 5 and 6 shells are sparse in energy or incomplete in transitions.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work (Dunseath et al 1999), by fitting the eigenphase sum we found the 1 P o shape resonance at 0.751 34 Ryd with a width of 1.55 × 10 −3 Ryd. By fitting the lifetime, we now find the resonance at 0.751 22 Ryd, lying between the two experimental values, with a width of 1.41×10 −3 Ryd, which is slightly narrower than that deduced from the measurements.…”
Section: Above the N = 2 Thresholdmentioning
confidence: 64%
“…Details of our method of propagating the R-matrix in two dimensions together with the parameters used in the calculation have been given in a previous paper (Dunseath et al 1999). Briefly, the R-matrix (the inverse of the logarithmic derivative matrix) is propagated in two dimensions in steps of 10 a 0 out to a distance of 100 a 0 , beyond which a one-dimensional propagation method (Light and Walker 1976) is used to obtain the R-matrix at some large distance r asy .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations